1983
DOI: 10.1530/jrf.0.0680219
|View full text |Cite
|
Sign up to set email alerts
|

FSH stimulation of the production of pyruvate and lactate by rat Sertoli cells may be involved in hormonal regulation of spermatogenesis

Abstract: Sertoli cells were obtained from 3\p=n-\6-week-oldrats, which were sterile after prenatal irradiation. The production of lactate by these Sertoli cells, measured 24\p=n-\48h after isolation during incubation in the absence of hormones, increased with age of the rats from 3 to 6 weeks. At all ages investigated, the production of lactate was enhanced in the presence of FSH plus testosterone, but the stimulation was most pronounced at 4 weeks of age. Lactate production was increased by FSH alone but testosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 20 publications
4
52
0
2
Order By: Relevance
“…Spermatogenesis is a complicated process involving both structural (Russell, 1980) and functional (Jutte et al, 1981;Jutte et al, 1983;Boltani et al, 1983) interactions between Sertoli cells and germ cells within the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spermatogenesis is a complicated process involving both structural (Russell, 1980) and functional (Jutte et al, 1981;Jutte et al, 1983;Boltani et al, 1983) interactions between Sertoli cells and germ cells within the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many metabolic products of Sertoli cells are required by the developing spermatogenic cells (Jutte et al, 1981;Jutte et al, 1983), and therefore may be a possible target through which lead might inhibit the process of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol phosphate dehydrogenase activity was not affected by any of the hormones tested. When Sertoli cells from 19-day old rats were incubated with [1,[2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate for 90 or 360 min, the [ 14 C] label was present predominantly in triglyceride and phospholipid fractions with minor amounts in other lipids. In Sertoli cells pretreated for 16 h with insulin and FSH, an increase in acetate incorporation into lipids was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The hormonal control of glycide metabolism in Sertoli cells is well known. In immature rats, folliclestimulating hormone (FSH) regulates the production of lactate, a preferential energy substrate for pachytene spermatocytes and round spermatids (7,8). Oonk et al (9) showed that insulin increases the rate of lactate production in vitro.…”
Section: Introductionmentioning
confidence: 99%